The Social Environment and Its Influence on Family Education - Dadang Jaya; Nessha Nur Kholifah; Ayu Wandira Al Munawar Zahrotusita (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
The social environment is a crucial factor influencing family education through the formation of children's values, behaviors, character, and learning achievement. This study aims to analyze the positive and negative impacts of the social environment on family education, examine its role in shaping family educational practices, explore the effects of technological advancements and social media on children's character development, and identify family strategies for optimizing the social environment to support children's education. This research employed a mixed-method approach combining library research and field research. Data were collected through a literature review of books, journal articles, previous research, interviews, and other scholarly works relevant to the research topic. The findings indicate that the social environment has an ambivalent influence, as it can both strengthen and weaken family education. The development of information technology, increasing individualism, and the growing flow of cross-cultural information have transformed the social environment from being local and homogeneous into one that is global, digital, and pluralistic. Effective family strategies for optimizing the role of the social environment include maintaining harmonious communication, providing moral role models, supervising social interactions, collaborating with communities and educational institutions, and utilizing technology wisely. Religious and cultural values serve as the fundamental foundation for creating a supportive social environment capable of fostering a generation that is morally upright, intellectually competent, and adaptable to social change.